Strength and Water Absorption of Concrete Containing Metakaolin and Nylon Fiber - Ismail, Mohd Hanif; Mohd Rusly, Noor Syuhaili; Deraman, Rafikullah (International Journal of Sustainable Construction Engineering and Technology, 2020)
The released of carbon dioxide during the manufacturing of cement is one of the factors that contributes various parties to participate in improving the performance of concrete. The aims of this study is to enhance the performance of existing concrete with the use of metakaolin (MK) and nylon (N) fibers in compressive, splitting tensile, flexural strength and water absorption rate. This study was conducted by comparing the results of control concrete samples with the concrete samples that use metakaolin by 5% and 10% by volume of cement and added with nylon fibers at 0.5% and 1.0%. Compressive, splitting tensile, flexural and water absorption tests were conducted to determine the strength of concrete and the concrete ability to absorb water. From this study it was found that the optimum percentage of metakaolin and nylon fiber was at 5% and 0.5%, which recorded at the highest strength when both materials were used in concrete with strength of 41.4MPa. At the end of this study, it shows that the compressive, splitting tensile, flexural strength and the rate of water absorption are influenced by the percentage of metakaolin and nylon fiber used in concrete mix.